Hero Stones (Memorial Stones) installed near the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
A row of hero stones (memorial stones) is installed near the Shiva Temple in the Morkhana village. This temple is a little away, to the north of the Suswani Mata Temple. The hero stones have depictions of male figures mounted on horses, sometimes along with a standing male figure in namaskar mudra (gesture of offering and devotion). Some of these are inscribed with dates from the 16th century CE.